Determining the power of mechanical losses in a rotary-piston engine - Mytrofanov, Oleksandr; Proskurin, Arkadii; Poznanskyi, Andrii; Zivenko, Oleksii (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports an experimental study into the magnitude of the power of mechanical losses of the prototype of a rotary-piston engine with an articulated cam mechanism for transforming movement, which was aimed at resolving the issue related to improving the efficiency of energy conversion. It has been experimentally established that the greatest component of the power of mechanical losses in a rotary-piston engine with an articulated cam motion transformation mechanism is friction losses. Depending on the rotational speed, they are about 68.4...74.4 % of total losses. The influence of the rotor rotation frequency on the total change in the power of mechanical losses and its components has been determined (an increase in the rotations by 3.75 times leads to an increase in the power of mechanical losses by 3.3 times). It is established that the rotation frequency of the rotor does not have the same effect on the power components of mechanical losses. Thus, an increase in the rotations by 3.75 times leads to an increase in friction losses by 3.0 times, and the component of losses on pumping strokes by 4.1 times. It was found that an increase in the pressure of working body by 2.0 times contributes to an increase in the mechanical efficiency of the rotary piston engine by 1.1 times. At the same time, it was determined that the rational speed range, which corresponds to the maximum values of the mechanical coefficient of efficiency, regardless of the pressure of working medium, is 800...1200 min–1. The resulting experimental data on studying the magnitude of the power of mechanical losses in the form of an analytical model of the influence of the main operational parameters of the rotary-piston engine with an articulated-cam mechanism for converting movement into a mechanical coefficient of efficiency have been generalized. The results reported here could make it possible to preliminary assess losses at energy conversion at the design stage and to construct a rotary piston engine for different purposes